Tseʾenah u-reʾenah – the Jewish Bible for Women: Between the Biblical Tradition and Folk Piety (with the Example of Bereshit) - Rybińska, Agata (Literatura Ludowa. Journal of Folklore and Popular Culture, 2020)
The aim of the article is to analyze the Jewish Bible for women (the first chapters of the book of Bereshit) and to argue for the egalitarian character of the text. Written in Yiddish, the vernacular language of the Eastern Jews, the book was intended to be used by women and men, especially those who did not know Hebrew. It is a compilation of biblical texts, rabbinical comments, and folk legends and explanations, aimed at shedding light on the religious issues and customs in a simple way that can be understood by people not educated in the Mosaic law.